Procaine Abrogates the Epithelial-Mesenchymal Transition Process through Modulating c-Met Phosphorylation in Hepatocellular Carcinoma - Yang, Min Hee; Mohan, Chakrabhavi Dhananjaya; Deivasigamani, Amudha; Chinnathambi, Arunachalam; Alharbi, Sulaiman Ali; Rangappa, Kanchugarakoppal S.; Jung, Sang Hoon; Ko, Hyejin; Hui, Kam Man; Sethi, Gautam; Ahn, Kwang Seok (Multidisciplinary Digital Publishing Institute (MDPI), 2022)
Simple Summary Epithelial-mesenchymal transition (EMT) is a vital process that leads to the dissemination of tumor cells to distant organs and promotes cancer progression. Aberrant activation of c-Met has been positively correlated with tumor metastasis in hepatocellular carcinoma (HCC). In this report, we have demonstrated the suppressive effect of procaine on the EMT process through the blockade of the c-Met signaling pathway. Procaine downregulated mesenchymal markers and upregulated epithelial markers. Functionally, procaine abrogated cellular migration and invasion. Moreover, procaine suppressed c-Met and its downstream signaling events in HCC models. We report that procaine can function as a novel inhibitor of the EMT process and c-Met-dependent signaling cascades. These results support the consideration of procaine being tested as a potential anti-metastatic agent. EMT is a critical cellular phenomenon that promotes tumor invasion and metastasis. Procaine is a local anesthetic agent used in oral surgeries and as an inhibitor of DNA methylation in some types of cancers. In this study, we have investigated whether procaine can inhibit the EMT process in HCC cells and the preclinical model. Procaine suppressed the expression of diverse mesenchymal markers but induced the levels of epithelial markers such as E-cadherin and occludin in HGF-stimulated cells. Procaine also significantly reduced the invasion and migration of HCC cells. Moreover, procaine inhibited HGF-induced c-Met and its downstream oncogenic pathways, such as PI3K/Akt/mTOR and MEK/ERK. Additionally, procaine decreased the tumor burden in the HCC mouse model and abrogated lung metastasis. Overall, our study suggests that procaine may inhibit the EMT process through the modulation of a c-Met signaling pathway.